Evaluasi Kepuasan Pengguna SIMPUS di Puskesmas Singotrunan Banyuwangi - Alfiansyah, Gamasiano; Putri, Monica Susantyas; Muna, Niyalatul; Farlinda, Sustin (Puslitbang Sinergis Asa Professional, 2024)
Singotrunan Banyuwangi Health Center started implementing the puskesmas management information system since 2010. There are still various obstacles in implementing SIMPUS, including incomplete and concise information content, no notification forms, system report Formats that are not up to date, the system still loads frequently at service, access to the report menu can only be done after 12 noon, there is no help menu in the system. The study aimed to assess user satisfaction using EUCS by descriptive study. The object was the SIMPUS application in all Singotrunan Banyuwangi Health Centers. The research subjects were all SIMPUS users at the puskesmas with a total of 21 respondents. The data analyze was performed by calculating the score and then collecting it into a criterion value. The study found that the criteria of good value with the proportion of the content aspect was 79.8%, the Accuracy aspect was 68.5%, the Format aspect was 73.7%, the timeliness aspect was 73.9%, the ease of use aspect was 75%. This states that SIMPUS is running well and necessary to be maintained, but there were still some deficiencies so it is suggested that it is necessary to improve the system through SIMPUS development by making the information content more concise and complete, adding warnings to forms, updating the report Format on SIMPUS, improving the system for minimize loading, provide flexible hours of access to process reports and add help menus or guides.